Influence of Thinking Ability About Discussion Method for Student Learning Achievement in PAI Lesson in SMP Negeri 18 Surabaya - Mus tofa; Mahsun Jayadi (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
Formulation of the problem of this research the researcher described as follows; 1. How is the application of learning strategies to improve the ability to think with the method of discussion in SMP Negeri 18 Surabaya ?; 2. How are student achievement in PAI subjects at SMP Negeri 18 Surabaya ?; 3. How does the effect of the application of learning strategies to increase the ability to think with the method of discussion on student achievement in the PAI (Islamic Religious Education )lesson at SMP Negeri 18 Surabaya? This research approach was a quantitative approach, the research population was all 7th grade students of SMPN 18 Surabaya, and the sample was 15% of the population, namely 45 students; Methods: observation, interview, documentation, and questionnaire, while analyzing the data using the statistical formula. "Product Moment" This formula showed a correlation between variable x, namely increased thinking ability with the method of discussion, and variable y, namely student achievement in PAI lesson. Research findings in this thesis were concluded. 1. The implementation of the learning strategy model for improving the ability to think with the discussion method at SMPN 18 Surabaya was quite good. Proven based on the results of the analysis through 85% percentage and the value were consulted with criteria determined by Suharsimi Arikunto between 76% - 100% which meant good. 2. Student achievement in the PAI lesson at SMPN 18 Surabaya was classified as Good. Based on the analysis of the percentage of 89.5% and the value were consulted with criteria determined by Suharsim Arikunto between 76% - 100% meant Good. 3. The effect of increasing the ability to think with the method of discussion on student achievement in Islamic religious education material there was a significant positive correlation, this was evidenced by the value of rxy or r0   that is 0.7841, then the value was consulted with an interpretation table that is between 0.70 - 0.90, which was classified as strong or high. So it can be concluded that learning to increase the ability to think with the discussion method was carried out well it improved student achievement in PAI lesson for students in SMP Negeri 18 SurabayaKeywords: Method, Achievement, and Influence